Novel nanostructure obtained from pacamã, Lophiosilurus alexandri, skin mucus presents potential as a bioactive carrier in fish - Charlie-Silva, Ives; de Melo, Nathalie Ferreira Silva; Gomes, Juliana M.M.; Fraceto, Leonardo Fernandes [UNESP]; Junior, Jose Dias Corrêa; Conceição, Katia; de Andrade Belo, Marco Antonio [UNESP]; Luz, Ronald Kennedy (Elsevier, 2019)
Nanoparticles to delivery drugs and immunomodulatory substances in fish have been widely studied by several research groups. In general, these nanoparticles are polymers, ceramic, fullerenes and metal derivates which can be toxic to fish and other aquatic organisms. We reported for the first time a nanostructured system composed of proteins obtained from pacamã fish (Lophiosilurus alexandri) mucus. We identified and characterized the formation of nanoparticles with 210.8 nm and zeta potential of −13.4 (mV). These characteristics suggest a possible application of this material as a biocompatible coating. These nanoparticles are biodegradable, metabolizable and can be easily manipulated; as well as they can easily undergo surface modification to transport biomolecules, thus exhibiting greater versatility. Our study suggests that these nanoparticles from fish mucus could be used to delivery drugs and to modulate the immune system, since they demonstrated to be biocompatible coating.
Keywords: Lophiosilurus alexandri; Mucus protein; Nanoparticles; Pacamã